The nauticAttiva project: A mobile phone-based tool for the citizen science plastic monitoring in the marine and coastal environment. (December 2022) - Scardino, Giovanni; Martella, Rocco; Mastronuzzi, Giuseppe; Rizzo, Angela; Borracesi, Quirino; Musolino, Flavio; Romanelli, Nicola; Zarcone, Salvatore; Cipriano, Giulia; Retucci, Andrea
Abstract: Plastic pollution is involving large coastal areas of the Mediterranean Sea. Innovative methods of plastic monitoring can be addressed through the citizen science approaches integrated with mobile phones. On the other hand, the availability of mobile phones is increasing among several users. Mobile phones can be integrated with a web mobile app, which allows to collect a lot of data for extended areas and in a short temporal range. In this study, the web service of iNaturalist was applied to implement a mobile phone-based tool to collect pictures of plastic items. At present, the web mobile app has been used to collect pictures of plastic debris in the Mediterranean Sea. Results were compared with the Mediterranean hydrodynamic regime, to highlight the pathways and densities of the plastic items. The proposed mobile phone-based tool represented a citizen science approach useful for the acquisition of plastic observations in the marine and coastal environment. Highlights: Mobile phone-based apps can be used in citizen science research. Plastic observations can be detected in the sea and coastal areas through a web mobile app. Assessment of litter density revealed a relevant amount of persistent floating plastic.